Characterising haemodialysis-associated cardiomyopathy using deformation imaging by cardiovascular magnetic resonance tagging and speckle-tracking echocardiography - Odudu, Aghogho (2013)
Haemodialysis patients represent an extreme phenotype of cardiovascular risk with a pattern of disease distinct from that in the general population. Non-traditional risk factors, specific to chronic kidney disease such as hypervolaemia, arterial stiffness and advanced glycation end-product deposition are increasingly recognised. A previously demonstrated non-traditional risk factor associated with worse outcomes is the presence of uraemic cardiomyopathy. This pattern of cardiac morphology and function has previously been defined as the presence of left ventricular abnormalities, including left ventricular hypertrophy, dilatation and left ventricular systolic dysfunction. For the first time the work in this thesis studies an incident haemodialysis population using multi-parametric strain-based imaging. This uses the accuracy of cardiovascular magnetic resonance imaging of resting cardiac and aortic morphology and function augmented with strain by tagging to longitudinal strain changes during haemodialysis by speckle-tracking echocardiography. The general aim of this thesis was to characterise the relationship of left ventricular function to haemodialysis using strain-based imaging. This might allow characterisation of haemodialysis-associated cardiomyopathy which may be distinct from the traditional definition of uraemic cardiomyopathy and may better define those patients who would benefit from modifications to the process of haemodialysis.